2019
DOI: 10.1177/0300891619839287
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder girdle impairment in breast cancer survivors: the role of range of motion as predictive factor for dose distribution and clinical outcome

Abstract: Background:Pain and functional impairment of the ipsilateral shoulder girdle in patients who underwent surgery and radiotherapy for breast cancer (BC) is a late complication reported in the literature. We analyze a correlation with dosimetric parameters and propose an algorithm for sparing strategies.Methods:A total of 111 patients treated for BC were included in this observational analysis during follow-up protocol visits. Exclusion criteria were the presence of moderate or severe arthrosis history and/or rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
6
1
1
Order By: Relevance
“…31 In our study, despite lower DASH scores on PO30 compared with the preoperative evaluation in the Limited ROM Group, the change was minimal. The same was noted by Marazzi et al, 32 who conducted an observational study with cross-sectional assessment in patients after conservative oncomammary surgery and radiotherapy, and found a mean DASH questionnaire score of 13.6 after treatment.…”
Section: Discussionsupporting
confidence: 79%
“…31 In our study, despite lower DASH scores on PO30 compared with the preoperative evaluation in the Limited ROM Group, the change was minimal. The same was noted by Marazzi et al, 32 who conducted an observational study with cross-sectional assessment in patients after conservative oncomammary surgery and radiotherapy, and found a mean DASH questionnaire score of 13.6 after treatment.…”
Section: Discussionsupporting
confidence: 79%
“…Orhan et al, (29) compared strength levels between the treated and untreated sides in BCS women, the results show that there is no difference in strength levels between the sides. In this same line Marazzi, et al, (30), also compared the strength levels between the affected and unaffected side, the results showed that there was no difference between the groups. Our results corroborate the studies by Marazzi et al, (30) and Orhen et al, (29), because we also found no difference between the groups (T = -1.196; p = 0.241).…”
Section: Discussionmentioning
confidence: 88%
“…In this same line Marazzi, et al, (30), also compared the strength levels between the affected and unaffected side, the results showed that there was no difference between the groups. Our results corroborate the studies by Marazzi et al, (30) and Orhen et al, (29), because we also found no difference between the groups (T = -1.196; p = 0.241). Muscle strength is one of the most important variables of an individual, since good strength levels increase the survival rate and prevent a number of diseases (31).…”
Section: Discussionmentioning
confidence: 88%
“…Altered movement of the shoulder complex is indeed already described in women following breast cancer surgery with a reported decrease in active range of motion in up to 84% of breast cancer survivors [4,[21][22][23]. In particular humerothoracic abduction and scapulothoracic lateral rotation motion can be affected [12,[24][25][26]. The presence and impact of these impairments each individually have already been described before [10].…”
Section: Introductionmentioning
confidence: 84%